2003
DOI: 10.1128/mcb.23.16.5726-5737.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Phosphatidylinositol 3-Kinase/Protein Kinase Akt Pathway Mediates Nitric Oxide-Induced Endothelial Cell Migration and Angiogenesis

Abstract: To test the hypothesis that the phosphatidylinositol 3-kinase (PI3 kinase)/protein kinase Akt signaling pathway is involved in nitric oxide (NO)-induced endothelial cell migration and angiogenesis, we treated human and bovine endothelial cells with NO donors, S-nitroso-L-glutathione (GSNO) and S-nitroso-N-penicillamine (SNAP). Both GSNO and SNAP increased Akt phosphorylation and activity, which were blocked by cotreatment with the PI3 kinase inhibitor wortmannin. The mechanism was due to the activation of solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
183
2
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(207 citation statements)
references
References 43 publications
11
183
2
11
Order By: Relevance
“…Addition of L-NMMA to cultures of BAECs attenuated the EET-and AA epoxygenase-induced migration and proliferation of these cells, suggesting that eNOS up-regulation may mediate, at least in part, the angiogenic effects of EETs. We also demonstrated that inhibitors of the PI3-kinase/Akt pathway significantly attenuated the EET-mediated angiogenic effects, consistent with the concept that the PI3-kinase/Akt pathway may mediate the angiogenic effects of NO (Kawasaki et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Addition of L-NMMA to cultures of BAECs attenuated the EET-and AA epoxygenase-induced migration and proliferation of these cells, suggesting that eNOS up-regulation may mediate, at least in part, the angiogenic effects of EETs. We also demonstrated that inhibitors of the PI3-kinase/Akt pathway significantly attenuated the EET-mediated angiogenic effects, consistent with the concept that the PI3-kinase/Akt pathway may mediate the angiogenic effects of NO (Kawasaki et al, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…NO and endothelium-derived hyperpolarizing factor represent the two major endothelial autacoids involved in the local control of vascular tone (Bauersachs et al, 1997). Importantly, the angiogenic effects of NO have been shown to be mediated by activation of the PI3-kinase/Akt pathway (Kawasaki et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). This mechanism agreed with the previous finding that EC expressed the constitutive eNOS through pathway to form NO and showed an increased migration in the process of angiogenesis [58]. A distinct signal generated by KDR, which influences cell migration by regulating cell adhesion via the assembly of vinculin on EC, has been found in a recent study [59].…”
Section: Discussionsupporting
confidence: 80%
“…The hypoxia-dependent angiogenic switch in human solid tumors is an early event linked to the secretion of high levels of VEGF and several angiogenic factors by cancer cells, as well as by endothelial cells or other cell types in the tumor stroma (Andre et al, 2000). The NO/cGMP/ PKG and calcium-dependent signaling pathways are also involved in the regulation of tumor cell invasiveness and angiogenesis linked to endothelial cell proliferation, morphogenesis, and tumor invasion (Kawasaki et al, 2003). These observations led to the hypothesis that hypoxic conditions could exert a direct or a permissive role on the PAR-1 invasive potential.…”
Section: Promotion Of Par-1 Proinvasive Activity By Hypoxiamentioning
confidence: 99%